1985
DOI: 10.1271/bbb1961.49.1551
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biological degradation of primary metabolites of atrazine by a Nocardia strain.

Abstract: The purpose of this paper is to elucidate the final degradative pathways of atrazine (I) by a Nocardia strain through experiments on the degradation of its metabolite, 4-amino-2-chloro-6isopropylamino-l ,3,5-triazine (Ha). This compound, in the bacterial medium, was transformed into several products identified as 2-chloro-4,6-diamino-l,3,5-triazine (lie), 4-amino-2-hydroxy-6isopropylamino-l ,3,5-triazine (VIII), 4-amino-l ,2-dihydro-l ,3,5-triazin-2-one (IV) and dicyanodiamidine (VII). The formation of (lie) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…Chemical hydrolysis results in the formation of hydroxyatrazine (HA) (24-26). Microbial degradation results in N-dealkylation (27)(28)(29)(30) to form deethylatrazine (DEA), deisopropylatrazine (DIA), and deethyldeisopropylatrazine (DEDIA) (57). Further degradation of dealkylated products results in formation of 4-amino-2-chloro-l,3,5-triazine (52).…”
Section: Results and Discussion: Metribuzinmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical hydrolysis results in the formation of hydroxyatrazine (HA) (24-26). Microbial degradation results in N-dealkylation (27)(28)(29)(30) to form deethylatrazine (DEA), deisopropylatrazine (DIA), and deethyldeisopropylatrazine (DEDIA) (57). Further degradation of dealkylated products results in formation of 4-amino-2-chloro-l,3,5-triazine (52).…”
Section: Results and Discussion: Metribuzinmentioning
confidence: 99%
“…Further degradation of dealkylated products results in formation of 4-amino-2-chloro-l,3,5-triazine (52). Hydroxylation of dealkylated products or dealkylation of hydroxylated products results in the formation of deethylhydroxyatrazine (DEHA), deisopropylhydroxyatrazine (DIHA), and deethyldeisopropylhydroxyatrazine (DEDIHA) (28,29). Complete degradation of atrazine to C0 2 has been observed through continued hydroxylation of the triazine ring to form ammeline, ammelide, and cyanuric acid prior to ring cleavage (57).…”
Section: Results and Discussion: Metribuzinmentioning
confidence: 99%
“…A number of studies have reported the isolation and the characterization of atrazinedegrading isolates (Behki et al, 1993;Bouquard et al, 1997;Devers et al, 2007aDevers et al, , 2007bGiardi et al, 1985;Mandelbaum et al, 1995;Rousseaux et al, 2001;Satsuma, 2006;Singh et al, 2004;Stamper et al, 2002;Strong et al, 2002;Struthers et al, 1998;Topp et al, 2000). Among the processes involved in the adaptation of the soil microflora to increasing atrazine degradation, horizontal gene transfer was shown to play a key role by favoring the exchange of the plasmid bearing the atz genes among the soil microflora (Devers et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The atrazine concentration decreased significantly, from 450 ng l -1 in Danube water to 50 ng l -1 in well water, though the total triazine concentration decreased only moderately (from 750 to 620 ng l -1 ). According to our current knowledge, the abiotic transformation of atrazine (for instance by photolytic hydrolysis; see below) yields only hydroxyatrazine; thus, the presence of dealkylated derivatives indicates the presence of endogenous atrazine-degrading microbial activity in the Danube sediment (Giardi et al, 1985).…”
Section: Concentration Of Atrazine and Atrazine Metabolites In The Damentioning
confidence: 98%